Academic Libraries in Support of Teaching During the COVID-19 - Grujic, Dragana (Qualitative and Quantitative Methods in Libraries, 2021)
The paper aims to provide an overview of how academic libraries helped conduct teaching at the university level during the first wave of the COVID-19 virus epidemic, in the period from mid-March (when a state of emergency was declared in Serbia) to mid-July 2020 (exam deadlines at most faculties). The research included the network of Belgrade University libraries (academic libraries, Central University Library “Svetozar Markovic“ and the Library of Students’ City Cultural Center) and has been conducted through online questionnaires. The results of the research indicate librarianship as a flexible profession adapting to new challenges. The pandemic has confirmed that libraries are an indispensable carrier of cultural development and distance learning. On the other hand, the study reveals certain shortcomings concerning academic library management and indicate issues that have to be improved in the future. In this way, the work can be a signpost on how academic libraries can further develop their services to more effectively support the teaching process.